Peraturan mengeja kata-kata Pinjaman Umum Dalam Ejaan Rumi Baru Bahasa Malaysia - Awang, Ahmad (Penerbit Universiti Sains Malaysia, 1981)
This paper describes the set of roles for Standardising common loan-words in romanized spelling in Bahasa Malaysia as agreed upon by Bahasa Malaysia Permanent Committee of the Ministry of Education, Malaysia.